Fluorite-related iridate Pr3IrO7: crystal growth, structure, magnetism, thermodynamic, and optical properties. (30th November 2022) - Kumar, Harish; Köpf, M; Ullrich, A; Klinger, M; Jesche, A; Kuntscher, C A
Abstract: Spin–orbit coupling in heavy 5 d metal oxides, in particular, iridates have received tremendous interest in recent years due to the realization of exotic electronic and magnetic phases. Here, we report the synthesis, structural, magnetic, thermodynamic, and optical properties of the ternary iridate Pr3 IrO7 . Single crystals of Pr3 IrO7 have been grown by the KF flux method. Structural analysis shows that Pr3 IrO7 crystallizes in an orthorhombic phase with Cmcm symmetry. The electron energy loss spectroscopy study indicates that Pr is in a 3+ valence state, which implies a 5+ oxidation state of Ir. Magnetization data measured at high and low magnetic fields do not exhibit any bifurcation between M ZFC and M FC, however, a weak hump in M ( T ) is observed at T ∗ ∼ 10.4 K. The specific heat data reveal two maxima at ∼253 and ∼4.8 K. The optical conductivity σ 1 ( ω ) spectrum shows 24 infrared-active phonon modes and reveals an insulating behavior with an optical gap Δ O P of size ∼500 meV. During cooling down, the temperature-dependent reflectivity spectrum reveals eight extra phonon modes below the structural phase transition (∼253 K). An anomaly is observed at around T ∗ in the temperature evolution of infrared-active mode frequencies suggesting the presence of significant spin–phonon coupling in the system.